Podejście konstruktywistyczne a rola nauczyciela w nauczaniu zdalnym języków obcych na przykładzie uczelni wyższej - Spychała-Wawrzyniak, Małgorzata (Neofilolog, 2023)
The aim of the article is to present the main directions of research in the field of constructivism and how we can use this educational model in remote language teaching. It should be noted that although constructivism is not a new approach in the theory of psychology and didactics, it turns out that it is not yet sufficiently present in educational practice, as we could see during the pandemic crisis. We pay special attention to the foreign language teacher who acts as a linguistic and cultural mediator. We assume, among other things, that a teacher, using constructivist ideas, can help heir students develop communication skills even more actively during remote classes. We will analyze the skills and characteristics of teachers who, above all, encourage and motivate their students to independently construct linguistic and cultural knowledge. Finally, we present the results of a pilot study conducted among first-year students of various philologies who have experienced remote language learning.